Biofunctional Nb/Ti-MCM-41 catalyst in oxidative acidic reaction of cyclohexene to diol - Ramli, Zainab (Malaysian Society of Analytical Sciences, 2007)

(untitled)
Bifunctional oxidative and acidic catalyst was prepared by incorporating titanium ion (Ti4+) and niobic acid in mesoporous molecular sieves MCM -41 structure. The catalyst is active both in oxidation, and acid-catalyzed reaction of olefin to diol. Nb/Ti-MCM-41 catalyst was prepared by first synthesizing Ti-MCM-41 by hydrothermal method, followed by subsequent impregnation of niobic acid (Nb) into Ti-MCM-41 at various %wt Nb loading. The framework structure of Ti-MCM-41 collapsed after incorporation of Nb but the tetrahedral form of Ti4+ still maintained with octahedral Nb species. Both Brønsted and Lewis acid sites are present in all Nb/Ti-MCM-41 samples. The formation of cyclohexanediol in the epoxidation of cyclohexene proved the bifunctional oxidative and acidic catalyst through the formation of cyclohexane oxide. The yield increased with the increase amount of the Brønsted acid sites provided by niobium species.